Art as biography in Felipe Cossio del Pomar - Sebastián Lozano, Pablo (Mercurio Peruano, 2018)
All human creation is nourished by experience in a unique, unrepeatable and inscrutable personal existence. But also in reverse: that existence is both the fruit of a sustained effort to make life itself an achievement that transcends its finitude and in which each of its achievements is the materialization of that desire.